KUA Transformation Towards Inclusive Marriage Registration: Criticism of the Minister of Religion's Proposal and Practical Challenges in Implementation - Ahyani, Hisam; Syamsudin, Syamsudin; Mutmainah, Naeli (Journal of Noesantara Islamic Studies, 2024)
This article discusses the proposed transformation for the Office of Religious Affairs (KUA) towards inclusive marriage registration in Indonesia. This proposal, submitted by the Minister of Religion, raises various questions and challenges regarding the effectiveness and relevance of this policy. Through a qualitative approach with literature studies and document analysis related to marriage registration policies, this article identifies criticisms directed at the Minister of Religion's proposal as well as practical challenges in its implementation. The results of the analysis show that there are various responses from the community and related parties to the transformation of the KUA, with criticism stating the relevance, effectiveness and social impact of the policy. Practical challenges in implementation include regulatory changes, increasing human resource capacity, and integration with other institutions in population administration. However, with a careful approach, the KUA has the opportunity to become an inclusive and effective marriage registration center in Indonesia.